Vpliv ortoz za gleženj in stopalo na ravnotežje - delni rezultati - Osrečki, Ksenija (Rehabilitacija (Ljubljana), 2013)
Background: The review of available literature shows no conclusive evidence of impact of the ankle-foot orthosis on balance. The purpose of the study was to determine the immediate impact of two different types of ankle-foot orthoses on the dynamic balance in persons with disabilities. Methods: 24 subjects who have visited the outpatient clinic for prosthetics due to the difficulties in walking were included in the study. Those expressing the will to participate were provided with an ankle-foot orthosis (either the first orthosis or a replacement). Using the Postural Response Assessment Device that artificially generates balance disorder, or perturbations,the participants dynamic balance was assessed with and without orthoses and compared with normative responses obtained from a healthy unaffected population. Results: All the participants demonstrated problems with maintaining balance. The serial ankle-foot orthosis made of polypropylene acted as a rear flexible spring and enabled a postural response more compliant with the norm after the forward and forward-lateral and backward and backward lateral perturbation in both the anterior-posterior and the mediolateral direction. The orthosis also had a minimum impact on the delay of the response. Custom-made orthosis from polypropylene enabled postural response with amplitudes within the norm, especially during perturbations on the affected side. Conclusion: Partial results indicate that the ankle-foot orthosis acting as a flexible rear spring can improve balance capabilities of the participants (immediately after or several years after the occurrence of the disorder), who tend to have difficulties with maintaining balance. The custom-made ankle-foot orthoses also demonstrated a positive impact on balance capabilities.
Keywords: ankle-foot orthosis; balance; gleženj; odzivi; ortoze; postural responses; ravnotežje; stopala